Bryophytes of Pico do Cuscuzeiro and Pico do Cardoso, São Paulo state, Brazil - Visnadi, Sandra Regina (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2011)
This paper presents the bryoflora of mountain peaks in the state of São Paulo (SP). Sixty-five species of bryophytes were found to occur on Pico do Cuscuzeiro (1,279 m), in Ubatuba, and 72 species on Pico do Cardoso (840 m), in Cananeia. Samples were collected of soil, rocks, the bark of living and dead phorophytes, and leaves between 1984 and 1995, with all material deposited in the Herbarium Maria Eneyda Pacheco Kauffmann Fidalgo (SP) and the Herbarium Rioclarense (HRCB). Hepatics and epiphytes collected on from single kind of substrate dominate the species list, which totals 107 species for both peaks surveyed. With the exception of Mytilopsis albifrons Spruce, the 106 remaining species all represent new records for São Paulo. Our checklist increases the list of bryophytes known to occur in mountain peaks across Brazil by 46%, making a new total of 180. The studied bryoflora is most similar to the bryoflora of the ‘paulista’ Atlantic rain forest than that one of peaks in other states of Brazil. Adelanthus carabayensis (Mont.) Grolle and Syzygiella integerrima Steph. are new records for the state of São Paulo.